Antioxidant and cytotoxic studies for kaempferol, quercetin and isoquercitrin - Vellosa, José Carlos Rebuglio; Regasini, Luis O. [UNESP]; Khalil, Najeh Maissar; Bolzani, Vanderlan da Silva [UNESP]; Khalil, Omar A.K.; Manente, Francine Alessandra; Netto, Harli Pasquini; De Faria Oliveira, Olga M.M. [UNESP] (FapUNIFESP (SciELO), 2011)
The aim of the present study was to investigate a cytotoxic oxidative cell stress related and the antioxidant profile of kaempferol, quercetin, and isoquercitrin. The flavonol compounds were able to act as scavengers of superoxide anion (but not hydrogen peroxide), hypochlorous acid, chloramine and nitric oxide. Although flavonoids are widely described as antioxidants and this activity is generally related to beneficial effects on human health, here we show important cytotoxic actions of three well known flavonoids. They were able to promote hemolysis which one was exacerbated on the presence of hypochlorous acid but not by AAPH radical. Therefore, despite they expected scavenger action over free radicals an oxidants, these compounds could be very lesive to living organisms by acting over erythrocytes and maybe other cellular types.
Keywords: Cytotoxicity; Flavonoids; Free radical; Oxidative damage